Foucault and Educational Ethics - Moghtader, Bruce; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
In his works on ethics, Foucault turned towards an examination of one's relationship with oneself and others. This differs from the modern approaches that explore the relationship between and the responsibilities of actors to each other by adopting criteria. Ethical criteria engender assumptions about the actors by focusing on their responsibilities. Instead of relying on criteria, Foucault's writing and lectures contributed to an awareness of the activities we take upon ourselves as ethical subjects. His reconstruction of the Greco-Roman ethics seeks to examine the possibilities of the reconstitution and transformation of subjectivity. Through this, he offers an avenue of understanding the formation of ethical subjects in their educational interrelationships.
Keywords: Education; Ethics; Philosophy and social sciences; Education -- Philosophy; Educational psychology; Education -- Psychology; Education; Educational Philosophy; Ethics; Moral Philosophy; Educational Psychology; Philosophy of Education; Electronic books